A putative multicopper oxidase, IoxA, is involved in iodide oxidation by Roseovarius sp. strain A-2. Issue 11 (2nd November 2015) - Shiroyama, Kanna; Kawasaki, Yasutaka; Unno, Yusuke; Amachi, Seigo
Graphical abstract: : Iodide oxidation by Roseovarius sp. strain A-2 grown on Marine Agar 2216 medium supplemented with iodide, starch and Cu 2+ . Abstract: Roseovarius sp. strain A-2 is an aerobic heterotrophic bacterium with a capacity for oxidizing iodide ion (I − ) to form molecular iodine (I2 ). In this study, iodide-oxidizing enzyme of strain A-2 was characterized. The enzyme was an extracellular protein, and Cu 2+ ion significantly enhanced the enzyme activity in the culture supernatant. When iodide was used as the substrate, the crude enzyme showed K m and V max values of 4.78 mM and 25.1 U mg −1, respectively. The enzyme was inhibited by NaN3, EDTA, KCN, and o -phenanthroline, and also had significant activities toward p -phenylenediamine and hydroquinone. Tandem mass spectrometric analysis of an active band excised from SDS–PAGE gel revealed that at least two proteins are involved in the enzyme. One of these proteins was closely related with IoxA, a multicopper oxidase previously found as a component of iodide-oxidizing enzyme of Alphaproteobacterium strain Q-1. Furthermore, a terrestrial bacterium Rhodanobacter denitrificans 116-2, which possesses an ioxA -like gene in its genome, was found to oxidize iodide. These results suggest that IoxA catalyzes the oxidation of iodide in phylogenetically distinct bacteria.